Statistical Optimization Using Response Surface Methodology for Enhanced Tensile Strength of Polyethylene/Graphene Nanocomposites - Wan Busu, Wan Nazri; Chen, Ruey Shan; Shahdan, Dalila; Mohd Yusof, Muhammad Jefri; Saad, Mohamad Jani; Ahmad, Sahrim (International Journal of Integrated Engineering, 2021)
Despite having remarkable features such as low density, ease of fabrication and recyclability, linear low-density polyethylene (LLDPE) has several drawbacks like poor stiffness and low creep resistance which fortunately can be improved by incorporating with other suitable nanofillers. In this study, graphene nanoplatelets (GNPs) that are well-known for its high surface area and superior stability were selected to reinforce the polymer network of LLDPE via melt blending. During mixing processing, the rotor speed, mixing temperature and mixing time parameters are manipulated with the aids of 5-level-3-factor central composite rotatable design (CCRD) in order to determine the optimization of processing parameters in preparing LLDPE/GNPs nanocomposites. The experimental data is fitted with the statistically significant quadratic model with R2 value of 0.8601. The results showed that the tensile strength of LLDPE/GNPs nanocomposites could be extended to 24.80 MPa.  The optimum processing parameters for preparation LLDPE/GNPs nanocomposites were found to be at 101 rpm rotor speed, 139.8oC of mixing temperature and 13.2 min of mixing time, resulting in LLDPE/GNPs nanocomposites with tensile strength of 24.11 MPa. Conclusively, our study has provided a novel statistical design of experiment to obtain the optimum processing parameters in preparing LLDPE/GNPs nanocomposites.